Law Enforcement of Human Rights (HAM) in Indonesia - Dahris Siregar; Grassela E Br Ginting; Hadirin Nduru; Sri Wenti Buulolo; Firman Yanus Hulu; Agustus Nduru; Indrawan Jaya Zalukhu; Sonitehe Halawa; Water Ade Putra; Jeremia G Aritonang (Jurnal Smart Hukum (JSH), 2023)
The article discusses law enforcement regarding human rights in Indonesia which is based on law number 39 of 1999. The author chose this title because until now law enforcement, especially related to human rights in Indonesia, is still not optimal, mainly because until now Indonesia is still in a transition zone which is still colored by legal uncertainty. The main issues in this article are: how is the application of law to human rights violations, which institution tries human rights violators, what means of settlement are used in cases of human rights violations in Indonesia, and what are the principles of Islamic law regarding human rights. In conclusion, human rights (HAM) are the basic rights possessed by humans in accordance with their work. Where every individual has his desire so that his Human Rights can be fulfilled. The human rights (HAM) of each individual are limited by the human rights of others. In Islam , Islam first pays attention to human rights (HAM). The emergence of violations of Human Rights (HAM) values, is motivated by an egoism which is concerned with personal or national interests, resulting in underestimating the values of Human Rights or other nations, resulting in a form of oppression or slavery in another form. In a state, human rights (HAM) are regulated and protected by the laws of the Republic of Indonesia, in which every form of violation of human rights (HAM) whether committed by a person, group, or tried in the implementation of human rights (HAM) trials . The Human Rights Court (HAM) takes court proceedings through the Human Rights court procedural law, as contained in the Law on Human Rights (HAM) courts. The concept of Human Rights (HAM) can be seen from two sides, including the western and eastern views.